1992
DOI: 10.1104/pp.99.3.808
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Dim-Red Light Leads to a Nongradient Pattern of Stem Elongation in Cucumis Seedlings

Abstract: Relative growth rate determinations on 5-millimeter regions of cucumber (Cucumis sativus L.) hypocotyls show that dim-red lightgrown seedlings have an even distribution of growth along the stem axis. This contrasts with the apical to basal graded decline in growth rate seen in dark-grown seedlings, including dark-grown cucumber seedlings used as controls in this study. Dark-grown seedlings convert to the nongradient pattern when transferred to dim-red light. The small amount of light required suggests that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Generally, plant elongation occurs in a gradient along the stem, with most growth occurring at the apex (Gotô and Suzuki, 1980;Martinez-Garcia and Garcia-Martinez, 1992;Shinkle et al, 1992). These results are consistent with our observation that hypocotyl growth in B. rapa occurs in a basipetal gradient.…”
Section: B Rapa Hypocotyl Growth Occurs In a Basipetal Gradientsupporting
confidence: 82%
“…Generally, plant elongation occurs in a gradient along the stem, with most growth occurring at the apex (Gotô and Suzuki, 1980;Martinez-Garcia and Garcia-Martinez, 1992;Shinkle et al, 1992). These results are consistent with our observation that hypocotyl growth in B. rapa occurs in a basipetal gradient.…”
Section: B Rapa Hypocotyl Growth Occurs In a Basipetal Gradientsupporting
confidence: 82%
“…Exactly where and how RIB could be integrated in this complex regulatory web is unclear at present, but it would affect IBA transport in response to light. Light has been shown previously to affect auxin transport in cucumbers (Shinkle et al, 1992), but also to specifically affect IBA transport in Arabidopsis (Rashotte et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Light quality, intensity, and direction can all affect auxin response and transport (Swarup et al, 2002). Dim red light was shown to cause an increase in polar auxin transport in cucumber (Cucumis sativus) hypocotyls (Shinkle et al, 1992). Steindler and coworkers (1999) have shown that shade-induced hypocotyl elongation was dependent on auxin transport, as it can be inhibited by NPA, and the auxin response mutant axr1-12 is defective in this response.…”
mentioning
confidence: 99%
“…Boxes were placed in 42-ϫ 27-ϫ 16-cm clear, plastic storage boxes with a 2-to 4-mm layer of distilled water on the bottom and with lids that were not tightly sealed, but that did limit evaporation. Storage boxes were placed in a growth room maintained at 24 Ϯ 1°C in complete darkness or under DRL at 0.5 mol m Ϫ2 s Ϫ1 , as described by Shinkle et al (1992), or in similar growth rooms at the University of North Carolina-Chapel Hill. Plants were grown for varying periods and transferred between darkness and DRL as indicated below and in "Results.…”
Section: Plant Materials and Light Treatmentsmentioning
confidence: 99%
“…To resolve this difficulty, we studied auxin transport using an intermediate state of photomorphogenesis induced by growth in continuous DRL (0.5 mol m Ϫ2 s Ϫ1 ). Under DRL plants exhibit an altered pattern of stem elongation, but an "etiolated" morphology is preserved (Shinkle et al, 1992). Seedlings grown under DRL have closed hooks, high hypocotyl elongation rates, and cotyledons that expand and green minimally.…”
mentioning
confidence: 99%